2021
DOI: 10.1115/1.4051530
|View full text |Cite
|
Sign up to set email alerts
|

A Normal Equation-Based Extreme Learning Machine for Solving Linear Partial Differential Equations

Abstract: This paper develops an extreme learning machine for solving linear partial differential equations (PDE) by extending the normal equations approach for linear regression. The normal equations method is typically used when the amount of available data is small. In PDEs, the only available ground truths are the boundary and initial conditions (BC and IC). We use the physics-based cost function used in state-of-the-art deep neural network-based PDE solvers called physics informed neural network (PINN) to compensat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The physics loss ensures that the system's governing equations are enforced. Various case studies and engineering problems where this approach has been applied can be found in [10,12,[63][64][65][66][67][68]. Additionally, Figure 11 illustrates a continuous PINN architecture demonstrating the physics-guided loss formulation.…”
Section: Physics-informed Neural Networkmentioning
confidence: 99%
“…The physics loss ensures that the system's governing equations are enforced. Various case studies and engineering problems where this approach has been applied can be found in [10,12,[63][64][65][66][67][68]. Additionally, Figure 11 illustrates a continuous PINN architecture demonstrating the physics-guided loss formulation.…”
Section: Physics-informed Neural Networkmentioning
confidence: 99%
“…For example, the nonlinear function F (u) = u ∂u ∂x (as in the Burgers' equation) leads to F (u)φ = ∂u ∂x φ + u ∂φ ∂x . Therefore, to solve the problem (15) by HLConcELM, the input training data (denoted by X) to the neural network is a Q×d matrix, consisting of the coordinates of all the collocation points, X = x p Q×d (for all x p ∈ X). The output data (denoted by U) of the neural network is a Q×m L matrix, representing the field solution u(x) on the collocation points, U = u(x p ) Q×m L…”
Section: Solving Linear/nonlinear Pdes With Hidden-layer Concatenated...mentioning
confidence: 99%
“…Interestingly, the authors set the number of hidden nodes to be equal to the total number of conditions in the problem. A solution strategy based on the normal equation associated with the linear system is studied in [15].…”
Section: Introductionmentioning
confidence: 99%